2021
DOI: 10.11591/ijaas.v10.i2.pp156-170
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater suitability for irrigated agriculture in Alluvial Bengal delta plain: Areview

Abstract: <p>Groundwater is a vital source of irrigation and domestic purposes in Bangladesh, and hence, it must satisfy the water quality guidelines. The study has selected eleven (11) Districts of Bangladesh and collect secondary data regarding the irrigation water quality of groundwater. Several irrigation water indices, such as soluble sodium percentage (SSP), sodium adsorption ratio (SAR), magnesium adsorption ratio (MAR), residual sodium carbonate (RSC), Kelly’s ratio (KR), permeability index (PI), and irrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Bangladesh has explored the IWQ in 14 zones Bangladesh (Islam & Mostafa, 2021c). The result of those studies exposed that the irrigation water of coastal regions such as the District of Sathkhira (Mirza et al, 2012), Borguna (Islam et al, 2016), Lakshipur (Bhuiyan et al, 2016), Khulna (Didar‐ul et al, 2017) and so on are extremely sodicity affected and those waters are not suitable for irrigation use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bangladesh has explored the IWQ in 14 zones Bangladesh (Islam & Mostafa, 2021c). The result of those studies exposed that the irrigation water of coastal regions such as the District of Sathkhira (Mirza et al, 2012), Borguna (Islam et al, 2016), Lakshipur (Bhuiyan et al, 2016), Khulna (Didar‐ul et al, 2017) and so on are extremely sodicity affected and those waters are not suitable for irrigation use.…”
Section: Resultsmentioning
confidence: 99%
“…The result of those studies exposed that the irrigation water of coastal regions such as the District of Sathkhira (Mirza et al, 2012), Borguna (Islam et al, 2016), Lakshipur (Bhuiyan et al, 2016), Khulna (Didar‐ul et al, 2017) and so on are extremely sodicity affected and those waters are not suitable for irrigation use. Another irrigation water of the east‐northern and northern regions of the country has a little salinity problem (Islam & Mostafa, 2021c). But this present study revealed that, except for EC and temporary Ca‐hardness problem, the irrigation water of the study zone is very good in position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suitability of water for irrigation uses is justified on the probable severity of hazard that can be predictable to develop during continuous use. The hazards that result differ both in kind and quantity and are adapted by soil, local climate, and plant, along with by the ability and knowledge of the irrigation activist (Islam & Mostafa 2021a;Rahim & Mostafa 2021). Thus, there is no usually bound on water quality; rather, its fitness for use is determined by the conditions of use that affect the accumulation of the water constituents and which may restrict crop yield.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%